Contemporary trends in utilization of metastasectomy in the era of targeted and immunotherapies - Passman, Jesse E.; Kallan, Michael J.; Roberson, Jeffrey L.; Ginzberg, Sara P.; Amjad, Wajid; Soegaard Ballester, Jacqueline M.; Tortorello, Gabriella; Fraker, Douglas; Karakousis, Giorgos C.; Bartlett, Edmund K.; Wachtel, Heather (Cancer, 2025)
Background Metastasectomy is a useful adjunct in the management of metastatic cancer. Widespread adoption of novel targeted and immunotherapies has improved the survival profiles of multiple malignancies, which has potentially altered the role of metastasectomy. This study aimed to characterize trends in metastasectomy across five primary cancers eligible for these therapies. Methods The National Inpatient Sample was used to identify patients who underwent metastasectomy in the United States (2016–2021). Patients with procedure codes for resection of the lung, liver, adrenal gland, brain, or small bowel and concurrent diagnosis codes for secondary malignant neoplasm of that site were included. Subjects were subcategorized by primary malignancy: colorectal cancer, lung cancer, breast cancer, melanoma, or renal cancer. Sample weights were used to produce national estimates, which were incidence adjusted by primary malignancy. Trends in utilization were calculated with average annual percent change (AAPC) and linear regression coefficients. Results Colorectal cancer was the most frequent indication for metastasectomy (n = 57,644 cases), followed by lung cancer (n = 55,090 cases), breast cancer (n = 12,616 cases), renal cancer (n = 8427 cases), and melanoma (n = 5658 cases). Utilization of metastasectomy increased over the study period for breast cancer (AAPC, +10.6%; p = .013) and melanoma (AAPC, +8.3%; p = .040) but did not change for lung cancer (AAPC, −1.6%; p = .26), colorectal cancer (AAPC, +0.3%; p = .83), or renal cancer (AAPC, +2.3%; p = .36). Conclusions Between 2016 and 2021, utilization of metastasectomy increased significantly for melanoma and breast cancer. The role of metastasectomy will likely continue to develop as new treatment protocols improve survival profiles for patients with metastatic disease. Between 2016 and 2021, metastasectomy utilization increased significantly for melanoma and breast cancer but remained stable for colorectal, lung, and renal cancers. Provision of metastasectomy shifted from urban nonteaching and rural hospitals to urban teaching hospitals, and admission charges increased; procedural outcomes including length of stay and inpatient mortality remained stable.